International Students’ Vocabulary Mastery and Language Confidence in Foreign Language Learning through Student-Centered Method (LSP International Journal, 2023)
Among the major problems faced by international students learning Malay language are the limitation of Malay language vocabulary mastery and the lack of confidence in Malay-language question and answer process. This research explores the effectiveness of the Two-Way Question-Answer method as an alternative method in building student’s vocabulary and confidence in Malay question-answer. The research involved 30 international post-graduate students of Malay Language Course 1 at Universiti Kebangsaan Malaysia (UKM). The research was conducted by action research where the data obtained through observation during intervention methods, comparison between conventional and intervention methods’ post test score as well as the linkages between variables in the questionnaire form. The data were analyzed using the Wilcoxon Sign Rank test for score comparison and Simple Linear Regression tests for the analysis of the association between variables. Results of the research shows that the participants build their vocabulary and self-confidence through a question-and-answer exercises during the intervention session. Comparison analysis between conventional and intervention cycle for both skills recorded a significant difference, with p value of 0.000 recorded by both. Regression analysis showed a significant association between intervention method for both targeted skills, with R Square/ R₂ values for vocabulary (0.751) and verbal answer method (0.711). This finding proves that the use of the Two-Way Question-Answer method has the potential to help second and foreign language learners increase vocabulary and confidence in foreign language